2006
DOI: 10.1097/01.ico.0000178728.57435.df
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Changes in Corneal Curvature in Keratoconus

Abstract: CLEK patients exhibited a slow but clear increase in corneal curvature. Younger age and poorer high-contrast manifest refraction visual acuity at baseline predicted the rate of change in corneal curvature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
82
1
6

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(93 citation statements)
references
References 15 publications
4
82
1
6
Order By: Relevance
“…27 Because of the convincing positive results in the first clinical study of collagen crosslinking, 24 comparison with a control group was ethically unacceptable. This is especially true in light of the Collaborative Longitudinal Evaluation of Keratoconus Study, 22,[28][29][30] which found a significant decline in vision within 8 years, an increase in astigmatism and corneal curvature, subepithelial scarring, and corneal thinning in untreated keratoconic corneas.…”
Section: Discussionmentioning
confidence: 97%
“…27 Because of the convincing positive results in the first clinical study of collagen crosslinking, 24 comparison with a control group was ethically unacceptable. This is especially true in light of the Collaborative Longitudinal Evaluation of Keratoconus Study, 22,[28][29][30] which found a significant decline in vision within 8 years, an increase in astigmatism and corneal curvature, subepithelial scarring, and corneal thinning in untreated keratoconic corneas.…”
Section: Discussionmentioning
confidence: 97%
“…Younger age and poorer high-contrast, manifest refraction visual acuity at baseline predicted an increased rate of change in corneal curvature (Table 3). [24] Of the 878 patients with at least one unscarred cornea at baseline, the five-year incidence of corneal scarring was 14% (120 of 878) overall, 17% (102 of 609) for contact lens-wearing eyes, and 38% (46 of 121) for contact lens-wearing eyes with corneal curvature greater than 52 D. Multivariate analyses of five-year prospective data from the CLEK Study cohort showed that younger age, baseline corneal curvature, contact lens wear, and corneal staining were predictive of incident corneal scarring (Table 4). [25] The eight-year incidence of penetrating keratoplasty was higher (15%) among patients less than 40 years old compared to patients 40 years old or older (8%).…”
Section: Longitudinal Findingsmentioning
confidence: 99%
“…Factors predictive of an increased risk of disease progression in keratoconus include young age (r35 years), steep keratometry, high astigmatism, reduced CDVA (irregular astigmatism), ethnicity other than white European, and documented progression in the contralateral eye. [37][38][39] These risk factors for disease progression are often present at presentation, and may be compounded if further disease progression is allowed to occur. Based on this, the proven efficacy of CXL, 14,18,19,21,22 the higher risk of CXL-related visual loss aged 435 years, 22 and the relative safety of transepithelial treatment, 33,34 we believe that there is a rational argument for transepithelial CXL at presentation for patients r35 years of age with keratometric stage II disease (Figures 2 and 3).…”
Section: Transepithelial Crosslinkingmentioning
confidence: 99%